ANALISIS PENGARUH PROMOSI JABATAN, MUTASI, DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR KARYAWAN DISTRIK NAVIGASI KELAS III CILACAP - Bella Melinda Rustandi; Candra Vionela Merdiana (Jurnal Fokus Manajemen Bisnis, 2019)
This study aims to determine the effect ofÂ  job promotion,Â  mutation and training on employee career development at â€œDistrik Navigasi Kelas III Cilacap". This research is a survey research using a questionnaire as an instrument. The population in this study consisted of 146 employees who worked at â€œDistrik Navigasi Kelas III Cilacapâ€. The sample in this study amounted to 115 employees â€œDistrik Navigasi Kelas III Cilacapâ€. The determination of sample size in this study uses the Isaac and Michael Tables (with an error tolerance of 5%). The sampling technique uses purposive sampling, which is sampling from the population with certain considerations. Test the validity of the instrument using CFA, while the reliability test results using Cronbach Alpha. The analysis technique used is multiple regression analysis techniques, and Hypothesis Test using F Test and t Test. The results of this study indicate that the variables of promotion, transfer and training simultaneously or jointly have a significant effect on employee career development in â€œDistrik Navigasi Kelas III Cilacapâ€. Job promotion variables have a significant effect on the career development of employees of the â€œDistrik Navigasi Kelas III Cilacapâ€. Mutation variables have no significant effect on career development of â€œDistrik Navigasi Kelas III Cilacapâ€ employees. And the training variables have a significant influence on the career development of the â€œDistrik Navigasi Kelas III Cilacapâ€.